When resilience becomes undesirable: a cautionary note - Hill, Yannick; Morison, Margaret; Westphal, Abbey; Gerwann, Solène; Ricca, Bernard P. (New ideas in psychology, 2024)
Traditionally, resilience has been viewed as a general positive adaptation to stressors. However, the hallmark of resilience - returning to the previous state following a perturbation - may also have severe downsides, which are often overlooked. Specifically, it may be unrealistic to return to the previous state or resilience may cause a person to become stuck in an undesirable state. In this article, we first call for a more nuanced theoretical conceptualization of resilience. To do so, we draw on insights from dynamical systems theory help to clearly define the role of a stressor and the idealized pathway to adapt to it. Then, we exemplify the potential downsides of resilience in the context of trauma and social adversity, learning, and goal-disengagement. In conclusion, researchers and practitioners should become more cautious with the term resilience and provide nuanced accounts for what they mean to avoid potentially harmful consequences.
Online verfügbar: 16. Februar 2024
Gesehen am 20.08.2024